Effect of intentional convection on the passivity of an Fe–6Cr surface in pH 4.5 Na2SO4 solution. (20th June 2020) - Fushimi, K.; Kanazawa, T.; Fujimura, A.; Kitagawa, Y.; Hasegawa, Y.; Doi, T.
Abstract: The anodic oxidation behavior of Fe–6Cr during potentio-dynamic polarization in pH 4.5 Na2 SO4 solution was investigated by electrochemical ellipso-microscopy. Active, passive, and trans-passive states of the Fe–6Cr surface showed heterogeneous oxidation behaviors depending on the substrate micro-structure, electrode potential and solution convection. Enhancement of mass-transport by solution injection in the latter half of the active state resulted in acceleration of passivation of the Fe–6Cr surface. The passivity-current density of the surface passivated by intentional convection was reduced to almost half of the current density of the surface that had been in the passive state in a stagnant solution, and the surface passivated by intentional convection showed better resistance against pitting in a chloride-containing solution. The improvement of passivity of the surface was attributed to the formation of a Cr-enriched passive film by a decrease in the thickness of the diffusion layer in the latter half of the active state.